In vitro Activities of Transition Metal Derivatives of Ketoconazole and Clotrimazole against a Wild Type Strain of Saccharomyces cerevisiae in Absence or Presence of Human Neutrophils - Navarro, Maribel; Colmenares, Ibis; Correia, Heriberto; Hernández, Alexandra; Ching, Yelitza; Millán, Yolanda; Ojeda, Luis E.; Velásquez, Mait; Fraile, Germán (Arzneimittelforschung, 2004)
In vitro activities of a series of gold, copper and ruthenium clotrimazole (CTZ, CAS 23593-75-1) and ketoconazole (KTZ, CAS 65277-42-1) derivatives were investigated individually and in combination with human neutrophils (PMNs) against a wild type strain of Saccharomyces cerevisiae. For 11 out of 12 tested metal complexes, the minimal inhibitory concentrations (MICs) at which 100 % of yeast growth was inhibited ranged from 0.75 to 3.0 µmol/L. The complex RuCl3(CTZ)3 · 2CH3OH (1f) (MIC = 0.75 µmol/L) was, although modestly, the only one able to increase the fungistatic activity of the parental drug (MIC = 1 µmol/L). On the other hand, at a sub-MIC concentration (0.5 µmol/L), the complexes [Cu(KTZ)Cl2]2 · 2H2O (2c) and RuCl2(KTZ)2 (2e) displayed synergistic fungicidal effects with PMNs whereas phagocytic capacity was enhanced by complexes [Cu(KTZ)3Cl2] (2b) and RuCl2(KTZ)2 (2e). The findings suggest that the metal-based agents may give rise to drugs with improved antifungal properties.
Keywords: CAS 23593-75-1; CAS 65277-42-1; Clotrimazole, in vitro studies, transition metal derivatives; Ketoconazole, in vitro studies, transition metal derivatives; Neutrophils, human; Saccharomyces cerevisia, wild type strain